Predaction activity of Diptera of the genus Medetera Fisher van Waldheim (Dolichopodidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Diptera of the genus Medetera Fisher von Waldheim (Dolichopodidae) are known chiefly for being forest species preying on Scolitidae (Coleoptera). This research was carried out to better understand the polyphagy and predation activity of the adults found for the first time in some greenhouses of Lombardia (ltaly). Many data about their ethology have been collected to estimate their potentiality as beneficials in pest biologica! control in such artificial environments.
Keywords: Diptera Dolichopodidae; Medetera; predation; ethology; greenhouses